Rhodium-catalyzed biheteroaryl-2-carbonitrile synthesis via double C–H activation. Issue 23 (22nd October 2019) - Xu, Hui-Bei; Zhu, Yan-Ying; Yang, Jia-Hui; Chai, Xin-Yue; Dong, Lin
Abstract : Rhodium(iii )-catalyzed double C–H activation and in situ dealcoholization to generate biheteroaryl-2-carbonitriles have been developed via a CDC mechanism, in which benzimidates act as both directing groups and the precursors of nitrile groups. Abstract : Rhodium(iii )-catalyzed double C–H activation and in situ dealcoholization to generate useful biheteroaryl-2-carbonitriles have been well developed via a CDC mechanism, in which benzimidates act as both directing groups and the precursors of nitrile groups. This simple and atom-economical method synthesizes various biheteroaryl-2-carbonitrile derivatives, which could be further transformed to more complex compounds.